Sondaż diagnostyczny w badaniach nad rolą różnic indywidualnych w procesie akwiz ycji jęz ykowej - Lesiak-Bielawska, Elżbieta Danuta (Neofilolog, 2010)
This article discusses the most popular diagnostic instruments employed when exploring the role of individual learner differences in foreign/second language acquisition. It thus focuses on the advantages and disadvantages of the quantitative research tradition, which relying on data recorded in numerical form, resorted to various inventories, but most importantly questionnaires designed for a specific research objective. In spite of their obvious drawbacks, highly structured questionnaires do not in any way seem to be devoid of certain research merits. However, since quantitative and qualitative research approaches represent different ways of thinking about and understanding the surrounding world, it is more advisable to adopt compromise in research, which will enable the researcher to place the phenomenon explored in a wider perspective.